Effect of Essential Oils Supplementation on Growth Performance, Nutrient Digestibility, Health Condition of Holstein Male Calves During Pre- and Post-Weaning Periods - Soltan, M.A. (Pakistan Journal of Nutrition, 2009)
One hundred Holstein male calves were assigned to investigate the effect of essential oil mixture (eucalyptus oil, menthol crystal, mint oil) supplementation in milk replacer (0, 94, 187 and 281 mg/calf/day) during the 8 weeks (pre-weaning period) and in drinking water (0, 15.6, 31.2 and 46.8 mg/liter) for the next 16 weeks (post-weaning period) on growth performance, nutrient digestibility, health condition as well as on some blood serum parameters. Calves receiving 94, 187 and 271 mg EOM/calf/day during pre-weaning period had lower (p>0.05) concentrate intake across the whole period by about 6.1, 6.1 and 1.2% respectively when compared with control but had no effect on roughage intake while reduced the total dry matter intake across the whole pre-weaning period by about 3.6, 3 and 1.2% respectively although, EOM had no effect on body gain and improved feed conversion ratio. EOM improve nutrient digestibility and increase total protein and albumin concentrations in the blood serum. Moreover, EOM treatment reduced the incidence of diarrhea, reduces the average number of diarrheic days and improves the general health score compared with the control. Although there were bad effects of the higher doses of EOM supplementation on health, it can be concluded that the supply of EOM reduced the necessity of antibiotics treatments against digestive and respiratory diseases. On the other hand, during post-weaning period it was clear from this study that calves administrated 15.6 mg of EOM/liter of drinking water may increase daily body gain, reduced feed intake and improved FCR by about 3.8, 3.2 and 8.15% respectively when compared with control while, the higher dose of EOM administration less effective and uneconomical to be used.